Ayat al-Qur’an dan Lirik Lagu Sufistik (Studi Intertekstual atas Album Bintang Lima Dewa 19) - Umar Bukhory (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2020)
The purpose of this manuscript is to browse the Qur'anic verses, which are positioned as a hipogram in the lyrics of “Bintang Lima”, Dewa 19’s album and the intertextuality pattern that occurs between the Qur'anic verses as a hipogram and the lyrics of “Bintang Lima” album as a transformation. The intertextual approach is used to evaluate which pattern is more used by the author of the transformation in ordering the lyrics of the song on the album. Of the twelve sentences in song lyrics on the “Bintang Lima” album, there are six sentences used exerp pattern, three sentences used modification pattern, one sentence used expansion pattern and two sentences used conversion pattern. The exerp patterns are more commonly used, as they are the simplest intertextual patterns and at the same time, giving way to the music fans of “Dewa 19” to understand sufistic messages in an easy way, so the accusations of carrying a Jewish mission (using Illuminati symbols). or theosofi and freemason understandings about this music group can be reconsidered.